Audit Delay pada Perusahaan LQ 45: Faktor-faktor yang Mempengaruhinya - Tikkos Sitanggang; Siti Mufidah; Juan Moses V. Sitanggang (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
This study aims to examine and analyze the factors that influence audit delay in LQ45 companies listed on the Indonesia Stock Exchange (IDX) in the period 2019-2023. The factors tested in this study consist of profitability, company size, company age, and size of public accounting firm. Secondary data used in this study comes from the annual reports of sample companies listed on the Indonesia Stock Exchange from 2019 to 2023. This study uses a quantitative approach. The population in this study consists of 45 companies, while the sample that can be used in this study is 18 companies. The data period used is 5 years so that the amount of data used in this study is 90. The data analysis method of this study is panel data regression analysis using Eviews software version 12. The results of this study indicate that company size and public accounting firm size have a negative effect on audit delay, while profitability and company age do not affect audit delay.